2015
DOI: 10.1186/s12936-015-0951-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced artemisinin yield by expression of rol genes in Artemisia annua

Abstract: BackgroundDespite of many advances in the treatment of malaria, it is still the fifth most prevalent disease worldwide and is one of the major causes of death in the developing countries which accounted for 584,000 deaths in 2013, as estimated by World Health Organization. Artemisinin from Artemisia annua is still one of the most effective treatments for malaria. Increasing the artemisinin content of A. annua plants by genetic engineering would improve the availability of this much-needed drug.MethodsIn this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…It has been recently shown that the transformation of A. annua with the rolB and rolC genes of Agrobacterium rhizogenes led to plants with an increased content of artemisinin ( Dilshad et al, 2015 ). The rol genes are known for their stimulatory action on plant secondary metabolism ( Bulgakov, 2008 ).…”
Section: Cannabis Trichomes: Small Factories Of Phytochemicamentioning
confidence: 99%
“…It has been recently shown that the transformation of A. annua with the rolB and rolC genes of Agrobacterium rhizogenes led to plants with an increased content of artemisinin ( Dilshad et al, 2015 ). The rol genes are known for their stimulatory action on plant secondary metabolism ( Bulgakov, 2008 ).…”
Section: Cannabis Trichomes: Small Factories Of Phytochemicamentioning
confidence: 99%
“…Protein of the rol A gene binds to DNA and stimulates growth, whereas the rol B gene is involved in the regulation of the auxin signal transduction pathway [ 15 ] and is a potent inducer of plant secondary metabolism, increasing the resveratrol production in Vitis amurensis [ 16 ] and anthraquinones in Rubia cardifolia [ 17 ]. The rol C gene encodes cytokinin glucosidase and stimulates the production of many secondary compounds in various plants [ 18 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…随着越来越多有价值的倍半萜化合物如抗疟疾的 青蒿素、显著抗癌活性的土荆芥内酯等 [22,23] 先后被发 现, 倍半萜的生物合成途径的研究日渐深入. 倍半萜合 酶在倍半萜的生物合成过程中起着至关重要的作用, 有实验证明, 通过过量表达倍半萜合酶基因可以提高 倍半萜化合物含量 [13,16] .…”
Section: 讨论unclassified